Does considering different cultures make online distance learning better? a study of stu-dent satisfaction - Melvin Ambida (Universidade Estadual de Alagoas, 2024)
As online distance learning (ODL) becomes a staple of modern education, ensuring student satisfaction with its frameworks is paramount. This study investigates the impact of cultural diversity on student satisfaction with various aspects of ODL. Employing a quantitative methodology, the study surveyed students to measure their cultural diversity awareness and satisfaction levels with ODL organization, course design, and technology. The findings indicate that students have a high level of cultural diversity awareness, with general weighted mean of 3.87 Satisfaction levels varied across different aspects of ODL. With organization receiving a mean score of 3.05, course design 3.16, and technology 2.94. A moderate positive correlation was found between cultural diversity awareness and satisfaction with ODL frameworks (r=.59 for organization, r=.54 for course design, and r=.49 for technology, all p<.05). furthermore, cultural diversity awareness was found to be a significant predictor of satisfaction with ODL frameworks, explaining 34% of the variance in organization satisfaction, 29% in course design, and 24% in technology satisfaction. These results highlight the critical role of cultural diversity awareness in enhancing student satisfaction with online distance learning and suggest that incorporating culturally responsive elements into ODL frameworks can significantly improve the online learning experience.